Design and Development of L-Shaped Rectangular Microstrip Patch Antenna With Slot for Wi-Fi 6E Applications - Belo, Jacinto Cipriano Ximenes; Zulkifli , Fitri Yuli (Universitas Indonesia, 2024)
This research focuses on designing and developing an L-shaped rectangular microstrip patch antenna with a ground slot optimized for Wi-Fi 6E applications. The goal is to ensure optimal performance in radiation efficiency, sufficient bandwidth, and signal reliability across the 2.4 GHz, 5 GHz, and 6 GHz frequency bands. Wi-Fi 6E, based on the 802.11a, 802.11b, and 802.11ax standards, offers speeds up to 11 Mbps, 54 Mbps, and 9.6 Gbps, respectively, and provides more channels with wider bandwidth and minimal interference, enhancing applications such as 4K/8K streaming, online gaming, and IoT. The antenna's design is crucial to exploit Wi-Fi 6E's potential, delivering optimal radiation efficiency, bandwidth, and signal reception. Measurement results show that the antenna's bandwidth in the first band ranges from 1.150 to 3.091 GHz (1941 MHz) and in the second band from 3.688 to 7.243 GHz (3555 MHz). The radiation pattern remains omnidirectional, and total efficiency is 82.27% at 2.436 GHz, 90.42% at 5.3 GHz, and 91.95% at 6.56 GHz. The gain is 4.19 dB at 2.4 GHz, 4.87 dB at 5 GHz, and 5.23 dB at 6 GHz. These results align with the simulations, making the proposed antenna a suitable candidate for Wi-Fi applications.